If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -8)(3x + 9) = 0 Reorder the terms: (-8 + 7x)(3x + 9) = 0 Reorder the terms: (-8 + 7x)(9 + 3x) = 0 Multiply (-8 + 7x) * (9 + 3x) (-8(9 + 3x) + 7x * (9 + 3x)) = 0 ((9 * -8 + 3x * -8) + 7x * (9 + 3x)) = 0 ((-72 + -24x) + 7x * (9 + 3x)) = 0 (-72 + -24x + (9 * 7x + 3x * 7x)) = 0 (-72 + -24x + (63x + 21x2)) = 0 Combine like terms: -24x + 63x = 39x (-72 + 39x + 21x2) = 0 Solving -72 + 39x + 21x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-24 + 13x + 7x2) = 0 Factor a trinomial. 3((-3 + -1x)(8 + -7x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(8 + -7x)' equal to zero and attempt to solve: Simplifying 8 + -7x = 0 Solving 8 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7x = 0 + -8 -7x = 0 + -8 Combine like terms: 0 + -8 = -8 -7x = -8 Divide each side by '-7'. x = 1.142857143 Simplifying x = 1.142857143Solution
x = {-3, 1.142857143}
| fx=-1x+x^3 | | 4/5=c/7 | | 3-x-9+15x= | | 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 |